2022
DOI: 10.1097/mao.0000000000003761
|View full text |Cite
|
Sign up to set email alerts
|

Is Gestational COVID-19 a Risk Factor for Congenital Hearing Loss?

Abstract: The aim of this study was to investigate whether COVID-19 during pregnancy is a risk factor for congenital hearing loss. Study Design: Retrospective cohort. Setting: Tertiary referral center. Patients: Hearing screening test results of 60,223 newborns between March 2020 and May 2021 were screened using the national database. Newborn babies of 570 pregnant women with positive COVID-19 PCR test during pregnancy who met the study criteria were included in the gestational COVID-19 group, and 570 healthy newborns b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…A study by Tanyeri Toker et al reported no significant association between COVID-19 infection during different trimesters and congenital hearing loss. Furthermore, similar to our study they have suggested that gestational COVID-19 infection is not associated with permanent congenital hearing loss [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study by Tanyeri Toker et al reported no significant association between COVID-19 infection during different trimesters and congenital hearing loss. Furthermore, similar to our study they have suggested that gestational COVID-19 infection is not associated with permanent congenital hearing loss [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Five studies [12,[14][15][16]18] compare the outcomes of COVID-19 groups with controls, which are defined as infants born from mothers without a positive COVID-19 test during pregnancy, with different findings. Mostafa, Oskovi-Kaplan, and Tanyeri Toker [14][15][16] did not define any difference between the COVID-19 and control groups, although they reported a more likely "refer" result at the first screening test in the COVID-19 group (which was then not confirmed at the retest) (see also Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, five of the selected studies presented a control group [12,[14][15][16]18]. It was interesting to notice a tendency to compare "refer" results at the first screening test in the COVID-19 group to controls, even though, at re-test, hearing loss was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite limited research in this area, several retrospective multicenter cohort studies have investigated whether exposure to COVID-19 in utero increases the risk of hearing loss in infants. To date, these studies suggest that intrauterine exposure to COVID-19 is not a risk factor to the development of hearing loss [27][28][29].…”
Section: Sars-cov-2 Infectionmentioning
confidence: 97%